1980
DOI: 10.1149/1.2129950
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sectioning and Surface Finishing of GaAs and GaSb

Abstract: The characteristics of a new anodic dissolution process for sectioning and removing damage from monocrystalline normalGaAs and normalGaSb are described. Dissolution proceeds in the presence of a solid anodic film, which limits local variations in etch rate, so the flatness and microtopography of initially smooth surfaces are preserved. The high anodic efficiency permits accurate monitoring of material removal. Etch rates may be varied from below 0.01 μm hr−1to over 10 μm hr−1 on normalGaAs and to 4 μm hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…16,17 The porous electrode was illuminated with a Schott KL 1500 halogen lamp at a potential of 0.8 V versus SCE in a conventional electrochemical cell. As electrolyte, a 0.1 M EDTA, 0.1 M Na 2 SO 4 solution was used and the pH was adjusted to 5 with H 2 SO 4 .…”
Section: The Origin Of Blue and Ultraviolet Emission From Porous Gapmentioning
confidence: 99%
“…16,17 The porous electrode was illuminated with a Schott KL 1500 halogen lamp at a potential of 0.8 V versus SCE in a conventional electrochemical cell. As electrolyte, a 0.1 M EDTA, 0.1 M Na 2 SO 4 solution was used and the pH was adjusted to 5 with H 2 SO 4 .…”
Section: The Origin Of Blue and Ultraviolet Emission From Porous Gapmentioning
confidence: 99%
“…This was achieved by continuous electrochemical etching, in the presence of a thick anodic oxide, at constant voltage. The technique is similar to that developed for GaAs by Faktor and Stevenson (6) and extended by the present authors (8). (It was shown that such a process Can remove material smoothly, while retaining the initial surface topography).…”
mentioning
confidence: 52%
“…The etching depth can be monitored using the coulometric information and local thinning can be perfectly controlled, even if very thin layers have to be removed. Note that an increase of the rate can be reached over one order of magnitude using complexing agents and/or solution stirring [7,31]. When very thick layers have to be removed the transfer limitation conditions can also be obtained using higher incident light power in the external pH windows for which a transfer between Gaussian to flat bottom profiles appears.…”
Section: Resultsmentioning
confidence: 99%
“…Anodic dissolution is used to perform accurate etching over a large range of etching rates and to give a damage-free final surface [6][7][8][9][10][11][12][13][14]. Anodic etching implies combined growth and dissolution of oxide, partly governed by electrochemical parameters [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%